Using Variable Perturbation Method to Study the Stability of Torsional Self-Excited Vibration in Main Drive System of Rolling Mill - Fenglan Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The self-excited vibration of blooming mill is a kind of torsional vibration, which occurs only when the rolling machine slips under appropriate conditions. Once in place, this may cause the larger peak pressure of each component in the main drive system; reduce the service life of the components, cause components′ damage directly. A large number of studies have shown that, at present there are not effective methods for diagnosis, monitoring of slipping and take proper measures in time to stop slipping so as to avoid the occurrence of malignant accidents. In this paper, author set out from another angle, take the main drive system of rolling mill as an example, to study stability of self-excited vibration. The conditions of the stable vibration are gained. By combining with the actual working conditions of blooming mill, author has put forward some effective measures to meet the stable conditions in order to make the blooming mill work in the stable state. Practice research has proved that the effective measures can contribute to reduce structural damage directly caused by the torsional vibration when “slipping” phenomenon occurred and to extend the service life of the components. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2699